Enhancement of mechanical properties of FSWed AA7075 lap joints through in-situ fabrication of MMC. (August 2017) - Buffa, Gianluca; Campanella, Davide; Fratini, Livan
Abstract: Friction Stir Processing (FSP) has been demonstrated feasible to create local Metal Matrix Composites (MMCs) in light alloys matrix. In this research, local MMCs were produced contextually to the weld using Friction Stir Welding (FSW). SiC particles were added to AA7075 lap joints by creating a proper groove on the top surface of the bottom sheet. Different welds were produced with increasing number of tool passes. The effect of the multiple passes was investigated through shear tests, macro and micro observations, average grain size and microhardness measurements. The welded joints were compared to a reference weld produced with no reinforcements. It was found that poor mixing between matrix and reinforcement phase is obtained with one tool pass. On the contrary, proper mixing is obtained with three tool passes, resulting in an increase in the maximum load in shear tests of 50% with respect to the reference conditions.